Influenza Virus-Induced Robust Expression of SOCS3 Contributes to Excessive Production of IL-6 - Liu, Shasha; Yan, Ruoxiang; Chen, Biao; Pan, Qidong; Chen, Yuhai; Hong, Jinxuan; Zhang, Lianfeng; Liu, Wenjun; Wang, Song; Chen, Ji-Long (Frontiers in Immunology, 2019)
Influenza A virus (IAV) remains a major public health threat in the world, as indicated by the severe pneumonia caused by its infection annually. Interleukin-6 (IL-6) involved excessive inflammatory response to IAV infection profoundly contributes to the virus pathogenesis. However, precise mechanisms underlying such a response are poorly understood. Here we found from both in vivo and in vitro studies that IAV not only induced surge of IL-6 release, but also greatly upregulated expression of suppressor of cytokine signaling-3 (SOCS3), the potent suppressor of IL-6-associated signal transducer and activator of transcription 3 (STAT3) signaling. Interestingly, there existed a cytokine-independent mechanism of the robust induction of SOCS3 by IAV at early stage of the infection. Furthermore, we employed SOCS3-knockdown transgenic mice (TG), and surprisingly observed from virus challenge experiments using these mice that disruption of SOCS3 expression provided significant protection against IAV infection, as evidenced by attenuated acute lung injury, a higher survival rate of infected animals and lower viral load in infected tissues as compared with those of wild-type littermates under same condition. The activity of nuclear factor-kappa B (NFκB) and the expression of its target gene IL-6 were suppressed in SOCS3-knockdown A549 cells and the TG mice after infection with IAV. Moreover, we defined that enhanced STAT3 activity caused by SOCS3 silencing was important for the regulation of NFκB and IL-6. These findings establish a critical role for IL-6-STAT3-SOCS3 axis in the pathogenesis of IAV, and suggest that influenza virus may have evolved a strategy to circumvent IL-6/STAT3-mediated immune response through upregulating SOCS3.